Data from the project "Pink coloring on the walls of Kristianopels kyrka", RAÄ-2024-1941 - Canosa, Elyse (Swedish National Heritage Board, 2025)
Data from the project "Pink coloring on the walls of Kristianopels kyrka" (Diarienummer RAÄ-2024-1941) including a sampling protocol. Data from the following analytical techniques is included: 1. Scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDS); 2. X-ray fluorescence spectroscopy (XRF); 3. Fourier transform infrared spectroscopy (FTIR); 4. optical microscopy. Instrument reports are also included. The intention of the project was to determine if a pink surface layer found on the walls of Krisitanopel church (https://bebyggelseregistret.raa.se/bbr2/byggnad/visaHistorik.raa?byggnadId=21400000441427&page=historik&visaHistorik=true) is a paint layer or due to a biological growth.
Keywords: Heritage science; SEM; FTIR; Microscopy; XRF; RAÄ-2024-1941; Kristianopels kyrka; History and Archaeology; Historia och arkeologi